Penerapan Media Audio Visual Pada Materi Siklus Air Untuk Meningkatkan Hasil Belajar Siswa SD - Pipih Nurhayati; Alvany Nur Miftahillah (ISLAMICA, 2020)
This study aims to find out: First, the application of learning using audio-visual media on natural science subjects of water cycle material in grade V of SDN Cirata. Secondly, differences in student learning outcomes after using audio-visual media in the science subjects of water cycle material in grade V SDN Cirata. Third, the response of students and teachers after using audio-visual media on natural science subjects’ water cycle material in grade V SDN Cirata. This research uses the Classroom Action Research (CAR) method. Data collection techniques using interviews, observation, tests and questionnaires. The conclusions of this study are: First, the steps of applying the use of audio-visual media using 3 stages, namely the preparation stage, the implementation phase and the follow-up stage. Second, before using audio-visual media in the pre-cycle stage the average score of students was 50 with mastery learning (7.69%) while in cycles I and II had used audio-visual media and an increase in learning outcomes. The first cycle of the average 63 students with mastery learning (43.59%) while in the second cycle the average value of students 77 with completeness (92.31%). Third, the response of students and teachers in the use of audio-visual media can be categorized as very agree. audio visual media is useful (91.03%), makes students better understand the material (92.95%), encourages students to be more focused (80.77%), students are more serious and test results increase (86.54%), make students more motivated (76.92%), and learning becomes more interesting (80.13%).